Constructing and designing a reluctance and initiative scale and its relationship to physical education female teachers participating in sports competitions in Maysan Governorate - Maitham Mutair Hamidi Al-Krizi (Gorontalo State University, 2025)
Reluctance and initiative are psychological dispositions that shape whether physical education teachers commit to the additional workload of preparing students for inter-school sports competitions, yet no validated instrument has previously captured these constructs among female physical education teachers, particularly in under-researched settings such as Maysan Governorate, Iraq, where women's school sport still struggles for institutional support. This study aimed to construct and validate a Reluctance Scale and an Initiative (reluctance-to-participate) Scale for female physical education teachers and to examine the relationship between the two constructs. A descriptive survey design with purposive sampling was used. An exploratory study involving 16 teachers (9 for the reluctance scale, 7 for the initiative scale) preceded a main study of 77 teachers (47 and 30, respectively), drawn from a research population of 93 physical education teachers in Maysan Governorate. The reluctance scale was built around four axes—self-confidence, optimism, positive thinking, and control/domination (32 items)—while the initiative scale comprised 20 items. Content validity ratios from a 13-member expert panel ranged from 84.6% to 100%, and Cronbach's alpha reached .913 (reluctance) and .903 (initiative). Teachers reported high self-confidence, optimism, positive thinking, and control, alongside a low tendency to withdraw from competitions, and all four axes correlated significantly and inversely with reluctance to participate. The scales are the first psychometrically validated tools for measuring reluctance and initiative among physical education teachers, with clear potential for extension to educators generally, supporting confident adoption in future research and professional development.